Effect of intensive agriculture-nutrition education and extension program adoption and diffusion of biofortified crops - Okello, J.J.; Kwikiriza, N.; Muoki, Penina Ngusye; Wambaya, J.; Heck, S. (Informa UK Limited, 2019)
Biofortification of staple crops to combat micronutrient deficiencies is gaining global recognition. Projects promoting biofortified food crops use intensive agriculture-nutrition education and extension activities to increase adoption of such crops. This study examines the effect of such programs on the adoption and diffusion of orange-fleshed sweetpotato (OFSP). It finds that intensive agriculture-nutrition education and extension programs adopted by some of the biofortification projects increases the adoption and diffusion of OFSP. Specifically, participation in mother-to-mother nutrition support clubs and nutrition-focused health talks affect its adoption and diffusion, but with varying degrees of importance. The paper discusses the implications of these findings.